ANALISIS KUANTITATIF KELENGKAPAN PENGISIAN FORMULIR INFORMED CONSENT RUMKITAL DR. RAMELAN SURABAYA - Aditya Dwi Arimbi; Indah Muflihatin; Niyalatul Muna (Politeknik Negeri Jember, 2021)
Completeness informed consent form of RUMKITAL Dr. Ramelan Surabaya is still less than the MinimumHospital Service Standard of 100%, it is based on a preliminary study of researchers that the incompleteinformed consent form on the identity component is 60%, important reporting is 80%, authentication is40%, and the correct documentation is 0%. The purpose of this study was to conduct a quantitativeanalysis of the completeness of the informed consent form of RUMKITAL Dr. Ramelan Surabaya. Thisstudy uses descriptive research with a cross-sectional approach to identify the completeness of filling outinformed consent. Data collection used is observation and documentation on the informed consent form.The results show the identification component with the highest completeness by 90% and the highestincompleteness by 55%; The important reporting component with the highest completeness is 80% andthe highest incompleteness is 80%; The authentication component with the highest completeness is 90%and the highest incompleteness is 50%; The correct documentation component with the highestcompleteness is 85% and the highest incompleteness is 50. Some suggestion to fix the problem is bymaking the Statement of Commitment, the SOP of evaluating and monitoring the medical recorddocuments completion, improving the Informed Consent SOP and Medical Records Completion SOP byadding completeness standard of informed consent filling which is must be achieved by RUMKITAL Dr.Ramelan Surabaya.